Universal Health Coverage: A Catalyst for Achieving 2030 Sustainable Development Goals - , O. Orjingene; , Ugo Okoli; , A. Adetunji-Hassan; , M. Ganama (Archives of Current Research International, 2022)
Background: Achieving Universal Health Coverage is one of the prerequisites for improved health outcomes, a decline in the rate of Impoverishment due to health expenditure (IHE), and achieving Sustainable Development Goals 1,2, and 3. While some countries (primarily those in Sub-Saharan Africa) are still battling to achieve Health Coverage for their populations, Western countries have achieved this feat using several strategies and models. This study aims to identify Universal Health Coverage implementation strategies adopted by different countries and how the strategies have contributed to achieving the 2030 Sustainable Development Goal targets. Method: A systematic literature review was employed, and a total of 10 studies conducted met our inclusion criteria. The sensitive search strategy was employed. The search was conducted with the use of appropriate keywords (guided by the research objective) in different databases such as MEDLINE (EBSCO), CINAHL (EBSCO), ProQuest, AMED (EBSCO), and PsycINFO. Articles were also retrieved through a manual search on google scholar. The search was also guided by the Population, Intervention, Comparison, Outcome PICO framework. Findings: Studies identified health insurance schemes for the unemployed, self-employed, and private sector employees and implementation of user fee exemption or subsidized medical bills for a population sub-group deemed vulnerable as Universal Health Coverage implementation strategies in different countries. These strategies significantly increased health coverage and improved health outcomes as well. Conclusion and Recommendations: The majority of countries in the sub-Saharan Africa region are yet to achieve Universal Health Coverage, this will pose a challenge to their ability to attain the 2030 Sustainable Development Goals. The study recommends that tested strategies such as improved health financing, sustainable health system strengthening, and a holistic approach to quality of healthcare services should be contextualized and implemented in countries that are yet to achieve Universal health coverage for their populations.